2023
DOI: 10.3390/cancers15020332
|View full text |Cite
|
Sign up to set email alerts
|

Cell-of-Origin Targeted Drug Repurposing for Triple-Negative and Inflammatory Breast Carcinoma with HDAC and HSP90 Inhibitors Combined with Niclosamide

Abstract: We recently identified a cell-of-origin-specific mRNA signature associated with metastasis and poor outcome in triple-negative carcinoma (TNBC). This TNBC cell-of-origin signature is associated with the over-expression of histone deacetylases and zinc finger protein HDAC1, HDAC7, and ZNF92, respectively. Based on this signature, we discovered that the combination of three drugs (an HDAC inhibitor, an anti-helminthic Niclosamide, and an antibiotic Tanespimycin that inhibits HSP90) synergistically reduces the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Studies have reported that inhibition of Class I and Class II HDACs, especially 1, 2, 4, and 6, using trichostatin A and sodium butyrate affects cell proliferation on the part of mir-204 and ERα in MCF7 and MDA-MB-231 cells [49][50][51]. Recently, a combination of HDACIs (entinostat + vorinostat + belinostat), anti-HSP90 inhibitor (tanespimycin), and anti-helminthic inhibitor (niclosamide) has been shown to synergistically inhibit cell proliferation in TNBC and inflammatory BC cell lines [52]. In a clinical phase II trial with 43 patients with ER+/PR breast tumors, a combination of SAHA/vorinostat and tamoxifen (a selective ER modulator) demonstrated a ~50% reduction in tumors [53].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that inhibition of Class I and Class II HDACs, especially 1, 2, 4, and 6, using trichostatin A and sodium butyrate affects cell proliferation on the part of mir-204 and ERα in MCF7 and MDA-MB-231 cells [49][50][51]. Recently, a combination of HDACIs (entinostat + vorinostat + belinostat), anti-HSP90 inhibitor (tanespimycin), and anti-helminthic inhibitor (niclosamide) has been shown to synergistically inhibit cell proliferation in TNBC and inflammatory BC cell lines [52]. In a clinical phase II trial with 43 patients with ER+/PR breast tumors, a combination of SAHA/vorinostat and tamoxifen (a selective ER modulator) demonstrated a ~50% reduction in tumors [53].…”
Section: Discussionmentioning
confidence: 99%
“…The known HDAC inhibitors can be structurally divided into three parts: (i) a cap-based group that identifies the HDACs’ active pocket; (ii) a zinc-ion-binding group (ZBG) that chelates zinc ions at the bottom of the catalytic pocket of HDACs; and (iii) a linking group that connects the cap-based group and the ZBG . As these HDAC inhibitors generally do not work well in solid tumors and are susceptible to drug resistance, they are usually used in combination with other drugs to maximize their potency and reduce the toxicity and side effects with low doses. , Thanks to a large hydrophobic zone on the surface of the HDAC protein, multitarget inhibition can be achieved when some functional groups or pharmacophores act as the cap-based group . Thus, HDAC inhibitors provide an excellent prototype for exploring and validating the concept of multitarget chimeric drugs.…”
Section: Introductionmentioning
confidence: 99%
“…38 As these HDAC inhibitors generally do not work well in solid tumors and are susceptible to drug resistance, 48 they are usually used in combination with other drugs to maximize their potency and reduce the toxicity and side effects with low doses. 49,50 Thanks to a large hydrophobic zone on the surface of the HDAC protein, multitarget inhibition can be achieved when some functional groups or pharmacophores act as the cap-based group. 38 Thus, HDAC inhibitors provide an excellent prototype for exploring and validating the concept of multitarget chimeric drugs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Epigenetic regulation of mRNA performs an important role in the occurrence and development of cancer 5 , 6 . Modification of m6A modification, one of over 100 chemical modifications, means that mRNA can be modified by methylation at the N6 position of adenine and has been reported to play a crucial role in tumorigenesis and progression 7 .…”
Section: Introductionmentioning
confidence: 99%